Analisis Kebijakan Politik Pendidikan Diindonesia - Supardi, Supardi; Fauzi, Anis; Fitri, Nurdina; Nuroniyah, Mila (Universitas Pakuan, 2025)
ANALYSIS OF EDUCATIONAL POLICY IN INDONESIAAbstract. The aim of this study is to analyze the quality of national education, which still poses various challenges, including inequality of access and poor quality of education. various factors affecting success or disability in implementing the guidelines and their impact on society and the education system. The results show that there are many initiatives, including compulsory education programs and training to improve teachers' skills. The gap between preparing guidelines and putting them into practice has proven to be a major obstacle. Therefore, more participatory strategies are needed as communities are also involved in the education policy planning process. Therefore, the implemented guidelines can actually respond to local circumstances and promote the overall improvement of education quality.